Pengaruh Penggunaan Genteng Kaca Terhadap Angka Kuman Udara Ruang Tidur di Dusun Karang Duren, Kalitirto, Berbah, Sleman Yogyakarta - Oka Prastyo Wijanarko; Sigid Sudaryanto; Y.B. Kamat Kartono (Poltekkes Kemenkes Yogyakarta)
One of the important rooms in a house is bedroom where people can use it for taking a rest or sleeping in a standard of eight hours/day. Based from a preliminary observation held at two bedrooms in Kalitirto Village, the number of microrganisms measured in the ambient air were 3592 colonies/m3and 3204 colonies/m3 respectively. These numbers did not fulfill the maximum number of microrganisms permitted for ambient air in a room i.e 700 colony/m3. Those high numbers of air microorganisms can affect household’s members’ health and furthermore can lead to the emerge of some diseases, such as Tuberculosis and AcuteRespiratory Infection. Because of this case, the study was aimed to decrase the numbers of the air microrganisms by installing glass roofs. The glass roofs were considered as effective media through which ultraviolet in sun rays can enter the rooms, and useful for reducing the number of the existing air microorganisms.The research was a true experimental study which used pre-test and post-test design. The research was conducted in 15 bedrooms, from which three groups of treatment consisted of five bedrooms were set. The sample bedrooms were installed by one, two and three glass roofs respectively. The data was analysed descriptively; and analytically by using paired t-test with sigificancy level at 0,05. The purpose of the research was to understand the influence of glassroofs installation on the number of microorganisms in ambient air of bedrooms, by comparing those numbers between treatment and control groups.Results of the research showed that the p-values generated for the decrease of the microrganisms numbers between the pre-test and post-test were: 0,003 (one glass roofs installation); 0,006 (two glass roofs installation); and 0,002 (three glass roofs installation). Therefore, it can be concluded that the installation of glass roofs on bedrooms affected the decrease of air microorganisms number.